Evaluasi Kegiatan Pengendalian dalam Keterlambatan Pengembalian Dana Pemberdayaan Ekonomi Masyarakat (PEM) pada Kelurahan Oeba, Kecamatan Kota Lama - Mariana Oktobeatrix Angesta Nogo Welan; Yolinda Yanti Sonbay; Antonius Y.W.Timuneno (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2025)
This study examines control activities in the delay in the return of Community Economic Empowerment (PEM) funds in Oeba Village, which is one of the policies of the Kupang City Government with interest-free funding assistance through the Community Empowerment Institution (LPM) of Oeba Village with the aim of developing productive businesses to increase the economic potential of the community. This study aims to determine the role of control activities in handling delays in the return of funds (PEM) and to determine the factors that cause the occurrence of arrears of funds (PEM) in Oeba Village, Kota Lama District. The type of data in this study is primary data obtained directly in the form of interviews with employees of the Community Empowerment Institution in Oeba Village. The data analysis technique used in this study is descriptive qualitative. The results of the study indicate that the delay in the return of funds (PEM) in Oeba Village is largely caused by weak supervision and performance reviews, in addition, inadequate human resource development and the absence of clear performance indicators hamper program evaluation. Factors causing PEM Fund arrears include business congestion, lack of understanding, minimal assistance to PEM fund recipients, poor financial management, and sanctions that are not strictly enforced